Brief Analysis of the Validation of Analytical Methods for Radiopharmaceuticals - Mengyi CHEN; Weihua CHENG; Hongyu LI (Journal of Isotopes)
Method validation is an important step to ensure the accuracy and reliability of analytical method，and is the basis for ensuring the controllable quality of drugs. Radiopharmaceuticals have the characteristics of radioactivity，short half-life，and small introduction，etc. The method validation guidance documents such as ICH Q2 (R1) and the four general rules of the Chinese Pharmacopoeia (9101) are not fully applicable to the validation of analytical methods for radiopharmaceutical. This paper discusses the validation of radioactivity analytical methods such as radionuclide identification，radiochemical purity，radionuclide purity，radioactivity (concentration)，in order to provide a reference for the validation of analytical methods during the development of radiopharmaceuticals.